Sedentary behavior and physical activity are independently associated with obesity in Brazilian adolescents: a quantile regression analysis: COMPORTAMENTO SEDENTÁRIO E ATIVIDADE FÍSICA SÃO INDEPENDENTEMENTE ASSOCIADOS À OBESIDADE EM JOVENS BRASILEIROS: UMA ANÁLISE DE REGRESSÃO QUANTÍLICA (Revista Contexto & Saúde, 2022)
Objective: to test the association of SB and moderate to vigorous physical activity (MVPA) with body mass index (BMI) in a representative sample of Brazilian young people. Methods: This is a cross-sectional school-based study (n = 1,023), including adolescents (14-21y; 54% female) from public and private schools in a Brazilian city. The survey was conducted in 2015 and the adolescents self-reported SB (screen time) and MVPA. Height and body mass were measured to calculate BMI. Quantile regression was used to investigate the association between SB, MVPA and BMI distribution percentiles (P10 ..., P90; statistical significance p
Keywords: Sedentary Lifestyle; Motor Activity; Nutritional Status; Cross-Sectional Studies